Discrimination between raw and ginger juice processed Magnoliae officinalis cortex based on HPLC and Heracles NEO ultra‐fast gas phase electronic nose. Issue 5 (22nd March 2022) - Zhang, Kewei; Wang, Jing; Fan, Xingchen; Zhu, Guangfei; Lu, Tulin; Xue, Rong
Abstract: Introduction: Magnoliae officinalis cortex (MOC), a traditional Chinese medicine, has been used in treating gastrointestinal diseases since ancient time. According to the Chinese Pharmacopoeia, it includes two kinds of decoction pieces, raw and ginger juice processed Magnoliae officinalis cortex (RMOC and GMOC). Objective: The aim of this paper was to study the differences between non‐volatile and volatile components in RMOC and GMOC. Methods: The non‐volatile components were detected by HPLC fingerprinting coupled with content determination (syringin, magnoflorine, honokiol and magnolol). Meanwhile, their odor information was obtained using a Heracles NEO ultra‐fast gas phase electronic nose to conduct radar fingerprint analysis, principal component analysis and discriminant factor analysis, and the volatile components were analyzed qualitatively by the Kovats retention index and the AroChemBase database. Results: The HPLC fingerprints were established and 20 common peaks were found in all chromatograms with similarity values of more than 0.900. The content determination results showed that the contents of syringin and magnoflorine decreased, while the contents of honokiol and magnolol increased in GMOC. By the gas phase electronic nose, the two decoction pieces could be distinguished obviously and 16 possible compounds were identified. Among them, the relative contents of (−)‐α‐pinene and β‐pinene increased, while β‐phellandrene and (+)‐limonene levels decreased. Conclusion: The results suggested that honokiol, magnolol, (−)‐α‐pinene and β‐pinene might be the main substances which could enhance the harmonizing effect on the stomach. Moreover, this paper could lay a foundation for exploring the processing mechanism of MOC and provide a novel method for the research of other traditional Chinese medicine with strong aroma. Abstract : RMOC and GMOC could be distinguished by HPLC and Heracles NEO ultra‐fast gas phase electronic nose. The non‐volatile components in them were detected by HPLC fingerprinting coupled with content determination, and the volatile components in odor were analyzed by a Heracles NEO ultra‐fast gas phase electronic nose firstly. The results showed that RMOC and GMOC shared similar compounds with different contents, honokiol, magnolol, (‐)‐α‐Pinene and β‐Pinene might be the main substances which could enhance the harmonizing effect on the stomach.